B-learning to Improve the Teaching and Learning process (Docentes 2.0 Journal, 2022)
During the last two years, Blended Learning has been a critical piece in promoting the benefits of technology in education, especially virtuality, which has allowed the teaching and learning process to emerge, which it maintained for an extended period for teachers and students at home. The objective of this article was to analyze some antecedents in the field of research on the implementation b-Learning, to guarantee improvements in the teaching and learning process once it has been developed at the Upper Secondary Level. The research was carried out under the systematic method, hermeneutical paradigm, qualitative approach, informative documentary type, and topical design, with which relationships were established and different positions were compared. The technique used was documentary research, and the instruments used were a matrix of state of the art and an analytical matrix of state of the art. The study found a wide variety of research focused on online learning and hybrid learning; however, the context and profiles of the students significantly modified the results and provided information for some gaps in the knowledge society, such as the need development of teaching skills for its implementation.
Keywords: B-learning; distance education; TIC; technological appropriation